Validity and practicality of integrated interactive digital timeline infographic learning media for mathematical thinking on the concept of metamorphosis - M. Arsyad; Ika Wardani (HAFECS PRESS, 2025)
The concept of metamorphosis can be taught through interactive digital timeline infographics that integrate mathematical thinking to practice numeracy literacy and technology skills, but existing media are generally not interactive and do not include these aspects. This study aims to test the validity and practicality of interactive digital infographic media integrated with mathematical thinking in material metamorphosis. This type of research is descriptive quantitative research as part of development research. The validation test and practicality test stages are part of the post-development stage in the Lee & Owens development model. The indicators of mathematical thinking integrated into the media include indicators of interpretation, representation, calculation, analysis, assumptions, and communication. The subjects for validation were three experts consisting of material experts, media experts, and language experts. The subjects for the practicality test were fourteen students who had taken embryology courses. The validation instrument and practicality test were developed by referring to the article published by Muliani in 2021. The data were in the form of quantitative data from validity scores and practicality tests, and qualitative data in the form of input to the validation process. The data were analyzed descriptively by calculating validity and practicality scores and matching them to validity criteria and practicality criteria. The results of the menu research. The results of the validity test of the interactive digital timeline infographic media on the metamorphosis of material were valid. The content validity aspect is included in the very valid category. The media and language construct validity aspects are included in the valid category. The results of the practicality test on the four aspects, namely the aspects of ease, time efficiency, benefits, and attractiveness, show that all aspects are included in the practical category. Abstrak. Konsep metamorfosis dapat diajarkan melalui infografis garis waktu digital interaktif yang mengintegrasikan berpikir matematis untuk melatih literasi numerasi dan keterampilan teknologi, tetapi media yang ada umumnya belum bersifat interakitf dan belum memuat aspek tersebut. Penelitian ini bertujuan untuk menguji validitas dan kepraktisan media infografis digital interaktif terintegrasi berpikir matematis pada materi metamorfosis. Jenis penelitian ini adalah penelitian kuantitatif deskriptif sebagai bagian dari penelitian pengembangan. Prosedur penelitian mengambil tahapan desain dan pengembangan pada model pengembangan Lee & Owens. Tahap uji validasi dan uji kepraktisan merupakan bagian dari tahap pasca pengembangan. Indikator berpikir matematis yang diintegrasikan pada media meliputi indikator interpretasi, representasi, kalkulasi, analisis, asumsi, dan komunikasi. Subjek untuk validasi adalah tiga orang ahli yang terdiri dari ahli materi, ahli media, dan ahli bahasa. Subjek uji kepraktisan adalah empat belas orang mahasiswa yang telah menempuah mata kuliah embriologi. Instrumen validasi dan uji kepraktisan dikembangkan dengan merujuk pada artikel yang dipublikasikan Muliani tahun 2021. Data berupa data kuantitatif dari skor validitas dan uji kepraktisan serta data kualitatif berupa masukan pada proses validasi. Data dianalisis secara deskriptif dengan menghitung skor validitas dan kepraktisan dan mencocokkan pada kriteria validitas dan kriteria kepraktisan. Hasil uji validitas media infografis garis waktu digital interaktif pada materi metamorfosis telah valid. Aspek validitas isi termasuk kategori sangat valid. Aspek validitas konsturk media dan bahasa termasuk kategori valid. Hasil uji kepraktisan terhadap keempat aspek yaitu aspek kemudahan, efisiensi waktu, keuntungan, dan daya tarik menunjukkan bahwa seluruh aspek termasuk kategori praktis.